PHASE AND FUNCTIONAL GROUPS ANALYSIS OF ZNO NANOCRYSTALLINE SYNTHESIZED FROM CITRUS ORANGE PEEL - Ma’arif, M. Samsul; Alfina, Fitria Tahta; Pratiwi, Devi Ragita Putri; Rohmawati, Lydia (Indonesian Physical Review, 2024)
The high production and market demand for citrus fruits can increase environmental waste. Most people do not use orange peel waste even though this peel contains bioactive compounds and phytochemicals that have the potential to form ZnO using the green synthesis method. This new research offers an environmentally friendly solution to reducing orange peel waste using abundant natural resources for nanotechnology applications. Therefore, this research aims to identify the phase of ZnO material and functional groups from orange peel extract. The extraction method of ZnO from Citrus sinensis orange peel uses green synthesis. The analysis in this research indicates that the sample has the phase of a zincite crystalline and a nanocrystalline size of 12.98 nm. The sample has an absorption peak at a wave number of 4000 – 400 cm-1 with functional groups indicating OH, C=C, Zn-OH, and Zn-O stretching vibration